일차섬유주절제술 후 처치에 따른 안압하강 효과 - 김은경; Eun Kyung Kim; 형성민; Sung Min Hyung (Daihan angwa haghoi jabji, 2005)
목적 : 일차섬유주절제술 후의 안압상승에 대한 단계적 처치에 따른 안압 하강 효과를 알아보고자 하였다. 대상과 방법 : 섬유주절제술 후 6개월 이상 추적 관찰이 가능했던 118명 136안을 대상으로 의무기록지를 후향적으로 분석하였다. 수술 후 안압이 상승했던 104안에서 단계적 처치(면봉 압박-공막봉합사 절단-needling-안압하강약물 추가)를 시행하여 각각의 안압조절효과를 알아보았다. 수술 후 면봉압박과 공막 봉합사 절단만으로 안압이 조절된 경우를 회복군으로 하였으며, 이들로써 안압이 조절되지 않은 경우를 비회복군으로 분류하여 결과를 분석하였다. 결과 : 평균 22개월의 추적 관찰 기간 중 전체 성공률은 80.1% 였고, 각각의 단계적 처치별 성공률은 11.8% (면봉 압박), 15.4% (공막봉합사 절단), 0.7% (needling), 28,7% (안압하강약물 추가)였다. 회복군에 비해 비회복군에서 수술전 안압이 높았고(p=.003), 당뇨가 있던 경우(p=.017)가 의미있게 많았다. 결론 : 일차섬유주절제술 후 전체 136안 중 32안(23.5%)에서 처치 없이 안압조절에 성공하였고 추가로 38안(27.9%)에서 단계적 처치를 시행함으로써 녹내장약제의 사용없이 성공적인 안압을 유지할 수 있었다. Purpose: To investigate the effect of stepwise procedures on high intraocular pressure (IOP) after trabeculectomy. Methods: A retrospective review was coducted on the medical records of patients who underwent trabeculectomy between January 1997 and December 2002. at the Chungbuk National University Hospital. Analysis included 136 eyes from 118 patients who received at least 6 months of follow-up care (mean 22.4±18.1 months). High IOP during the early postoperative period was identified in 104 of the 136 eyes, and these were treated by the following methods in a stepwise manner: ① cotton-tip application (a slow, steady eyeball pressure with a sterile cotton tip was favored), ② scleral flap suture cutting (26-gauge needle), ③ needling of the bleb (without antimetabolites), ④ additional antiglaucoma medication. If none of the above management techniques was successful, the surgery was repeated. After cotton tip application or scleral flap suture cutting, patients were divided into the recovery group (IOP was reduced) and the non-recovery group. Results: Success rates were 11.8% for cotton-tip application, 15.4% for scleral flap suture cutting, 0.7% for needling without antimetabolites, and 28.7% for additional antiglaucoma medication. The overall success rate was 80.1%. Pre-interventional factors associated with the non-recovery group were higher preoperative IOP (p=0.003) and diabetes (p=0.017). Conclusions: Four procedures were used, in a stepwise manner, to reduce IOP following trabeculectomy. IOP was found to decrease to desirable levels without the use of antiglaucoma medication in 27.9% of all subjects. KCI Citation Count: 0